Dental anxiety and behavioral problems: A study of prevalence and related factors among a group of Iranian children aged 6-12 - M Paryab; M Hosseinbor (Wolters Kluwer Medknow Publications, 2013)
Purpose: The aims of this study were to assess the prevalence and also some related demographic and dental factors of dental anxiety and behavioral problems in school-aged children. Subjects and Methods: A total of 150 children of 6-12 years old were selected according to the inclusion criteria. Prior to the dental visit, the mothers were asked to answer a questionnaire of dental and demographic background and a Corah dental anxiety scale (CDAS). At the same time, a faces version of the modified child dental anxiety scale (MCDAS) was completed by the child. Next, the child was guided to the operating room. According to the treatment plan, local anesthesia solution was injected and the child's cooperative behaviors were quantified based on the Frankle index duration the injection stage. Analysis of Variance and Linear regression models were used for the statistical analysis. Results: The mean scores of the child's dental anxiety and cooperative behavior were 20.81 (±6.97) and 3.04 (±0.86), respectively. Forty four children (29.33%) had severe dental anxiety. Child's age and regular dental visit are predictive factors for the child's dental anxiety (P < 0.05). Dental behavioral problems had been identified in 43 children (28.67%). Unpleasant previous dental experience is an important factor affecting the child's cooperative behaviors (P < 0.05). Conclusion: High prevalence of severe dental anxiety may be seen in early years of school. It seems that general factors such as family factors have less impact on behavior of school aged children in a dental visit.